2021
DOI: 10.3389/fcimb.2021.753320
|View full text |Cite
|
Sign up to set email alerts
|

The Angiostrongylus vasorum Excretory/Secretory and Surface Proteome Contains Putative Modulators of the Host Coagulation

Abstract: Angiostrongylus vasorum is a cardiopulmonary nematode of canids and is, among others, associated with bleeding disorders in dogs. The pathogenesis of such coagulopathies remains unclear. A deep proteomic characterization of sex specific A. vasorum excretory/secretory proteins (ESP) and of cuticular surface proteins was performed, and the effect of ESP on host coagulation and fibrinolysis was evaluated in vitro. Proteins were quantified by liquid chromatography coupled to mass spectrometry and functionally char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…3 Currently, the mechanism of coagulopathy in A. vasorum patients is not entirely known; however, hyperfibrinolysis and hypofibrinogenaemia remain a consistent finding. 3,4,12,13 Emesis is a known side effect of tranexamic acid usage, 14 and may represent a contraindication to patients with the potential for intracranial bleeding and/or vasculitis due to risk of increasing intracranial pressure with vomiting; however, previous studies have shown that 1 mg/kg maropitant intravenously can completely abolish emetic events at up to 50 mg/kg of tranexamic acid. 15 Fortunately, the largest scale study to date documented a low rate of adverse events, occurring in only 1.7% of dogs and 3% of cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Currently, the mechanism of coagulopathy in A. vasorum patients is not entirely known; however, hyperfibrinolysis and hypofibrinogenaemia remain a consistent finding. 3,4,12,13 Emesis is a known side effect of tranexamic acid usage, 14 and may represent a contraindication to patients with the potential for intracranial bleeding and/or vasculitis due to risk of increasing intracranial pressure with vomiting; however, previous studies have shown that 1 mg/kg maropitant intravenously can completely abolish emetic events at up to 50 mg/kg of tranexamic acid. 15 Fortunately, the largest scale study to date documented a low rate of adverse events, occurring in only 1.7% of dogs and 3% of cats.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that not all patients with A. vasorum infection present with coagulopathy, and not all patients that present with bleeding have hyperfibrinolysis 3 . Currently, the mechanism of coagulopathy in A. vasorum patients is not entirely known; however, hyperfibrinolysis and hypofibrinogenaemia remain a consistent finding 3,4,12,13 …”
Section: Discussionmentioning
confidence: 99%
“…15,50,51 Several hypotheses have been offered, including development of DIC, thrombocytopenia, hyperfibrinolysis or, more recently, complex interactions between host's homeostasis and A. vasorum surface proteins. [52][53][54] Young dogs are more likely to be infected by the parasite, especially due to their exploratory behaviour; however, studies on the impact of age at the time of infestation or parasitic burden on the development of bleeding diathesis are lacking. 5 DIC is the excessive activation of haemostasis, which can eventually result in haemorrhage by consumption of platelets and coagulation factors.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…In fact, humans having a low to moderate degree of ongoing fibrinolysis, with increased fibrinolytic markers, such as plasmin/α2-PI complex, D-dimer, and tPA, escaping identification by ROTEM [ 52 ]. More recently, to overcome this problem, tPA-modified TEG and ROTEM assays were developed and were found to be more sensitive in revealing fibrinolysis, both in humans and dogs [ 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Assays for D-dimer and FDPs are both available in veterinary [ 61 , 62 , 63 , 64 , 65 ] and human medicine [ 52 ].…”
Section: Detection Of Fibrinolysis In Clinical Practicementioning
confidence: 99%